2022
DOI: 10.3390/antiox11081453
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heme Oxygenase 1 Expression upon a Primary Exposure to the Respiratory Syncytial Virus and a Secondary Mycobacterium bovis Infection

Abstract: The human respiratory syncytial virus (hRSV) is the leading cause of severe lower respiratory tract infections in infants. Because recurrent epidemics based on reinfection occur in children and adults, hRSV has gained interest as a potential primary pathogen favoring secondary opportunistic infections. Several infection models have shown different mechanisms by which hRSV promotes immunopathology to prevent the development of adaptive protective immunity. However, little is known about the long-lasting effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Cannedo-Marroquin et al described the increase in the lung HO-1 expression of mice primarily infected with human respiratory syncytial virus (hRSV) and subsequently with a Mycobacterium bovis (M. bovis) strain referred to as Bacillus Calmette-Guerin (BCG) [1]. In a series of elegantly performed experiments, the study showed that a pre-infection with hRSV promoted lung pathology such as increased infiltration of innate immune cells, including interstitial and alveolar macrophages, during a subsequent mycobacterial challenge, thus impairing pulmonary immune responses and promoting secondary mycobacterial colonization, which was also associated with increased lung tissue HO-1 expression.…”
mentioning
confidence: 99%
“…Cannedo-Marroquin et al described the increase in the lung HO-1 expression of mice primarily infected with human respiratory syncytial virus (hRSV) and subsequently with a Mycobacterium bovis (M. bovis) strain referred to as Bacillus Calmette-Guerin (BCG) [1]. In a series of elegantly performed experiments, the study showed that a pre-infection with hRSV promoted lung pathology such as increased infiltration of innate immune cells, including interstitial and alveolar macrophages, during a subsequent mycobacterial challenge, thus impairing pulmonary immune responses and promoting secondary mycobacterial colonization, which was also associated with increased lung tissue HO-1 expression.…”
mentioning
confidence: 99%